REMEDIES TO TIMELY DELIVERY OF CONSTRUCTION PROJECTS IN LUSAKA, ZAMBIA – AN EXPLORATORY STUDY - Mulenga MUKUKA; Clinton AIGBAVBOA; Wellington THWALA (Journal of Construction Project Management and Innovation)
The construction industry is a key sector in the development and economic growth of Zambia, however, the industry has not escaped the challenges facing other countries worldwide in terms of deliveri ng construction projects on time as stipulated in the contracts. This paper assesses the construction professionals’ perception on the measures of minimising constuction project delays in Lusaka Zambia. The data used in this paper were derived from both primary and secondary sources. The secondary data was collected via a detailed review of related literature. The primary data was collected through a well structured questionnaire which was distributed to construction professionals, which include: Architec ts, quantity surveyors, builders, civil engineers, land surveyors and project managers. Out of the 50 questionnaires sent out, 32 were received back representing 64% response rate. Data received from the questionnaires was analysed using descriptive statis tics procedures. Findings from the study revealed that site management and supervision, effective strategic planning, clear information and communication channels, use proper and modern construction equipment and proper project planning and scheduling were the major measures of minimising construction project delays. The study contributes to the body of knowledge on the subject of minimising construction project delays in Lusaka, Zambia.